Overwintering strategy in Pyrrhocoris apterus (Heteroptera): the relations between life-cycle, chill tolerance and physiological adjustments - Kostál, V; Simek, P (Journal of insect physiology, 2000)
Seasonal dynamics of ecophysiological parameters are described which are relevant to overwintering in field-collected adults of a Czech population of the red firebug, Pyrrhocoris apterus. Five life-cycle phases were distinguished using the duration of pre-oviposition period as a criterion: reproductive activity (spring-early summer), intensification of reproductive diapause (RD) (peak of summer), maintenance of RD (late summer-early autumn), termination of RD (late autumn-early winter), and low temperature quiescence (LTQ) (winter). The supercooling capacity and chill tolerance (c.t.) increased simultaneously with the termination of RD and all three processes were triggered/conditioned by autumnal decrease in ambient temperatures. Maximum supercooling capacity and c.t. 'outlived' the end of diapause and persisted throughout the LTQ state. The limits of c.t. were estimated as -15 degrees C/1-2 weeks for 50% survival. Ribitol, sorbitol, arabinitol, and mannitol were accumulated in the winter-sampled insects. Relatively low concentrations of polyols (dominating ribitol reached ca. 1% FW) indicate that they do not function as colligative cryoprotectants. However, because their seasonal occurrence coincided with the highest c.t., their non-colligative cryoprotectant effects would merit further study. Although the overwintering microhabitat of P. apterus is buffered, the temperatures may fall to -13 degrees C during exceptionally cold winters and thus, the parameters of c.t. seem to be just appropriately tuned to the local overwintering conditions.